2017
DOI: 10.1108/lhtn-10-2016-0051
|View full text |Cite
|
Sign up to set email alerts
|

Drupal, TEI and XML: How to prototype a digital humanities tool?

Abstract: Purpose This paper aims to take seriously the import accorded to the interface within the digital humanities. It will probe some of the possibilities and limits of the computer interface as a reading and research tool by unpacking theoretical and practical aspects of interface design. Design/methodology/approach The authors wanted to see if they could design a tool that would meet three interrelated goals: the first was to develop a digital tool that would enable scholarship rather than mere publishing. Next,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A new digital tool could solve the past humanities research problems. Monte and Serafin (2017) indicated that the first and most salient theme that emerged in digital humanities research is the requirement of digital reading and research tools. To effectively support digital humanities research, Chen and Tsay (2017) proposed a novel collaborative annotation system (CAS) with four types of multimedia annotations including text annotation, picture annotation, voice annotation and video annotation, which can embed with any HTML web pages to enable users to collaboratively add and manage annotations on HTML web pages and provide a shared mechanism for discussing about shared annotations among multiple users.…”
Section: Introductionmentioning
confidence: 99%
“…A new digital tool could solve the past humanities research problems. Monte and Serafin (2017) indicated that the first and most salient theme that emerged in digital humanities research is the requirement of digital reading and research tools. To effectively support digital humanities research, Chen and Tsay (2017) proposed a novel collaborative annotation system (CAS) with four types of multimedia annotations including text annotation, picture annotation, voice annotation and video annotation, which can embed with any HTML web pages to enable users to collaboratively add and manage annotations on HTML web pages and provide a shared mechanism for discussing about shared annotations among multiple users.…”
Section: Introductionmentioning
confidence: 99%